Surgıcal Treatment Of Tmj Internal Derangement (Case Report) - Orhan Güven (Galenos Yayinevi, 1993)
Internal derangement of the TMJ can be defined as an abnormal relationship of the disc to condyle, fossa, and articular eminence. The disc is usually displaced anteromedially. Internal derangement is a common problem of the TMJ. Conservative splint theraphy is applied for the preventive treatment in the patients with anterior disc displacement. The surgical treatment of TMJ internal derangement consists of two basic principles; disk repositioning and disc removal. Several variations of these two procedures may he performed. In this paper, a case of internal derangement and its surgical treatment is presented.